An Assistance in the grand design planning of Sendang Mudal Edupark in Sawangan Village - Hanani, Tri; Handziko , Rio Christy (Universitas Ahmad Dahlan, 2024)
This activity aims to, initially provide a clear picture regarding the steps to realizing the Sendang Mudal Edupark in Sawangan Village. In addition give more insight and provide a new perspective in the development of one of the tourist destinations in Sawangan, namely Sendang Mudal. The activities that took place consisted of discussions, surveys of tourism potential locations, designing the grand design of the Edupark and outreach. This activity produced several outputs including: first, the lecturers’ activities in Sawangan Village went well, smoothly, and according to the plan. Second, the grand design of the Edupark design provides various alternatives for development of “Sendang Mudal” for next five years. Third, the motivation and enthusiasm of village officials to take part in the discussion and socialization of the Sendang Mudal Edupark was very high because the responses give by the participants were very active during the training process. Fouth, participants feel happy and satisfied with this activity and hope the similar activities can be carried out on an ongoing basis.